Extreme Antimicrobial Peptide and Polymyxin B Resistance in the Genus Burkholderia - Loutet, Slade A.; Valvano, Miguel A. (Frontiers in Cellular and Infection Microbiology, 2011)
Cationic antimicrobial peptides and polymyxins are a group of naturally occurring antibiotics that can also possess immunomodulatory activities. They are considered a new source of antibiotics for treating infections by bacteria that are resistant to conventional antibiotics. Members of the genus Burkholderia, which includes various human pathogens, are inherently resistant to antimicrobial peptides. The resistance is several orders of magnitude higher than that of other Gram-negative bacteria such as Escherichia coli, Salmonella enterica, or Pseudomonas aeruginosa. This review summarizes our current understanding of antimicrobial peptide and polymyxin B resistance in the genus Burkholderia. These bacteria possess major and minor resistance mechanisms that will be described in detail. Recent studies have revealed that many other emerging Gram-negative opportunistic pathogens may also be inherently resistant to antimicrobial peptides and polymyxins and we propose that Burkholderia species are a model system to investigate the molecular basis of the resistance in extremely resistant bacteria. Understanding resistance in these types of bacteria will be important if antimicrobial peptides come to be used regularly for the treatment of infections by susceptible bacteria because this may lead to increased resistance in the species that are currently susceptible and may also open up new niches for opportunistic pathogens with high inherent resistance.